2012
DOI: 10.1002/jgm.1652
|View full text |Cite
|
Sign up to set email alerts
|

CHM/REP1 cDNA delivery by lentiviral vectors provides functional expression of the transgene in the retinal pigment epithelium of choroideremia mice

Abstract: Lentiviral CHM/REP1 cDNA transgene rescues the prenylation defect in CHM mouse RPE and thus could be used to restore REP1 activity in the RPE of CHM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…component (12)(13)(14)(15). These experimental conditions fail to recapitulate the cellular and molecular environment of diseased photoreceptors in patients who have a complex spatial distribution of stages of disease across the retina (Fig.…”
Section: Significancementioning
confidence: 99%
“…component (12)(13)(14)(15). These experimental conditions fail to recapitulate the cellular and molecular environment of diseased photoreceptors in patients who have a complex spatial distribution of stages of disease across the retina (Fig.…”
Section: Significancementioning
confidence: 99%
“…Despite these favorable factors, the main challenge in developing gene therapy for choroideremia at present remains the lack of an animal model that accurately reflects the human condition. Recently, it has been reported that subretinal injections of a lentiviral CHM/REP1 cDNA transgene resulted in efficient transduction of the RPE, longterm expression for at least 6 mo and a rescued prenylation defect in the CHM mouse (Tolmachova et al 2012). An open-label, dose-escalation phase 1 clinical trial is being undertaken in Oxford University to assess the safety and tolerability of the AAV2.REP1 vector administered at two different doses to the retina in 12 choroideremia patients (see http://ClinicalTrials.gov .identifier: NCT01461213, PI: Rob McLaren).…”
Section: Gene Therapymentioning
confidence: 99%
“…Correction of mutant phenotypes was nevertheless observed in both the photoreceptor and RPE cells, near the injection site. Expression was detected up to 3 weeks after injection ( [12] and unpublished observations), and it is expected that it would be retained longer [15].…”
Section: Hiv-derived Vectorsmentioning
confidence: 90%